2022
DOI: 10.3390/ijerph19020751
|View full text |Cite
|
Sign up to set email alerts
|

Do School-Level Factors Affect the Health Behaviors of High School Students in Korea?

Abstract: We conducted a multilevel analysis to identify the individual- and school-level factors that affect Korean high school students’ tooth brushing, soda intake, smoking, and high-intensity physical activity. We sampled 27,919 high school students from the 15th Korea Youth Risk Behavior Web-Based Survey. The individual-level variables included demographic, socioeconomic, and health-related factors. The school-level variables included school system and school type. Regarding the individual-level factors, economic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…are a particularly relevant population for the study of the (re)production and reinforcement of smoking-related inequalities. They are indeed evolving away from the denormalisation process and are at a higher risk of smoking (Atorkey et al, 2021;Chyderiotis et al, 2020;Hanke et al, 2013;Kwak et al, 2022;Looze et al, Ibid.). In Germany (Montag et al, 2015) and France (Spilka et al, 2018), studies have shown, for example, that the proportion of 'apprentices' who smoke on a daily basis is, respectively, 40.7% and 47.3%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are a particularly relevant population for the study of the (re)production and reinforcement of smoking-related inequalities. They are indeed evolving away from the denormalisation process and are at a higher risk of smoking (Atorkey et al, 2021;Chyderiotis et al, 2020;Hanke et al, 2013;Kwak et al, 2022;Looze et al, Ibid.). In Germany (Montag et al, 2015) and France (Spilka et al, 2018), studies have shown, for example, that the proportion of 'apprentices' who smoke on a daily basis is, respectively, 40.7% and 47.3%.…”
Section: Introductionmentioning
confidence: 99%
“…are a particularly relevant population for the study of the (re)production and reinforcement of smoking-related inequalities. They are indeed evolving away from the denormalisation process and are at a higher risk of smoking (Atorkey et al, 2021; Chyderiotis et al, 2020; Hanke et al, 2013; Kwak et al, 2022; Looze et al, Ibid. ).…”
Section: Introductionmentioning
confidence: 99%